Radykalno-hermeneutyczne pojęcie „ekscesu” jako świętowanie codzienności. Na materiale powieści „Испуг” Władimira Makanina - Krzysztof Tyczko (Studia Rossica Posnaniensia)
This article proposes a novel interpretation for Vladimir Makanin’s Ispug, based on the findings of radical-hermeneutical philosophy. The radical-hermeneutical approach is also considered a philosophical worldview, which coincides with the attitude evoked by Makanin’s compositions. The prismatic inspection of the novel Ispug is undertaken using the category of excess.